Cover Image, Volume 30, Issue 2. (19th March 2020) - Unknown
Abstract: The cover image is based on the Original Article Semistatic and Sparse Variance‐Optimal Hedging by Di Tella et al., https://doi.org/10.1111/mafi.12235 .